Big Data dan Penguasaan Pasar dalam Pengambilalihan Usaha Digital: Komparasi Rezim Hukum Persaingan Indonesia dan Jerman - Samariadi, Samariadi; Firmanda, Hengki; Ervansyah, Fauzan; GM. Manik, Rahmat (Zaaken: Journal of Civil and Business Law, 2026)
The digital economy has positioned Big Data as a primary strategic asset that creates new market entry barriers in the form of "data fortresses." The assessment of company acquisitions in this sector demands a paradigm shift from physical asset parameters to data control parameters. This study aims to analyze and compare the approaches employed by the Business Competition Supervisory Commission (Komisi Pengawas Persaingan Usaha/KPPU) of the Republic of Indonesia and the German Federal Cartel Office (Bundeskartellamt) in evaluating data access. The research employs a normative juridical method with a comparative law approach. The findings reveal that the KPPU continues to rely on traditional quantitative parameters, such as sales-based market share indicators (HHI), which have demonstrably exhibited gaps in detecting data-driven market power, as evidenced in the case of TikTok's acquisition of Tokopedia. In contrast, the Bundeskartellamt has adopted explicit qualitative criteria through Section 18(3a) of the Gesetz gegen Wettbewerbsbeschränkungen (GWB) to assess data access and network effects, as illustrated in the Parship-ElitePartner case. It is concluded that the KPPU must reform its assessment guidelines by incorporating data access as a primary qualitative factor to ensure fair competition in the digital market.